2015
DOI: 10.1007/s10826-015-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Children with Intellectual and Developmental Disabilities in Asian Indian Families in the United States

Abstract: Asian Indian immigrant parents of children with intellectual and developmental disabilities (IDD) have unique experiences and challenges grounded within their cultural contexts and migration to United States. This study sought to describe these experiences using qualitative method. Open-ended interviews were individually conducted with 15 Asian Indian parents (8 mothers, 7 fathers) whose children were diagnosed with Down Syndrome, Autistic Disorder, or Pervasive Developmental DisorderNot Otherwise Specified. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 30 publications
3
46
0
1
Order By: Relevance
“…Immigrant families also used social support services such as schools, social workers, and interpreting services to target their specific problems (Croot et al, ). Asian Indian immigrant parents in the United States stated that when they were able to access resources in the school or in the community, they felt less lonely and their needs were being met (Zechella & Raval, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrant families also used social support services such as schools, social workers, and interpreting services to target their specific problems (Croot et al, ). Asian Indian immigrant parents in the United States stated that when they were able to access resources in the school or in the community, they felt less lonely and their needs were being met (Zechella & Raval, ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings revealed that immigrant parents who received social and emotional support from their family seemed to be resilient. Other parents who received instrumental support, such as being employed in a professional job, speaking English fluently, earning a high income, having a driver’s license, or being more educated, appeared more resilient (Heer et al, ; Su, ; Zechella & Raval, ). A combination of two or more of these resources led to more resilient parents (Su, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some mothers reported that their husbands did not understand the disability or wish to access services as they had been raised in a different culture overseas and had different values and beliefs about disability. However, Zechella and Raval () found that some couples' relationships were strengthened as a result of raising a child with a disability because they put their small differences aside and the responsibility became the focus.…”
Section: Resultsmentioning
confidence: 99%
“…The parents were aware that not only does the child get ‘labelled but the whole family is described for life as “the family with the disabled child, man, or woman”’. For this reason some mothers were advised by community members to keep their child's disability a secret and ‘not bring him out as he's not supposed to be seen’ (Zechella & Raval, ), and were told that disclosing a diagnosis could jeopardise the child's future chance of getting married. One mother described how she rejected the diagnosis and treated her son ‘like a normal child’ but kept him hidden from the community (McLeod, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation